Empiricism - Bongiorno, F; Parrott, M (Routledge, 2023)
Delusions are found across a wide range of medical and psychiatric conditions. Yet not all people with these conditions develop delusions. So what makes the difference between those that do and those that don’t? There is a large and continuing multidisciplinary literature on this question with many competing explanations. So, it has become common practice to group explanations into clusters based on theoretical similarities. The most widely accepted classificatory scheme, proposed by John Campbell, distinguishes two theoretical paradigms, empiricism and rationalism. The central theoretical commitment of empiricism is that delusions are caused by anomalous sensory experiences. Over the last two decades, empiricism has firmly established itself as the dominant approach to explaining delusions. The ‘empiricism’ label, though, obscures as much as it reveals. Empiricists may agree that experiences causally generate delusions, but they may nevertheless differ on what they take the role of experience to be. In the first part of this chapter, we identify three ways in which empiricists may conceptualise the role of sensory experience in the development of delusions (as a source of justification, as a mere part of causal mechanism, or as a source of meaning). In the second part, we contrast these varieties of empiricism with rationalism and with other, non-empiricist, theoretical frameworks. By clarifying different types of empiricism, we hope to show that there are many different theoretical approaches to understanding delusions.